Transforming healthcare analytics : the quest for healthy intelligence - Lewis, Michael N.; Nguyen, Tho H., 1972- (Hoboken, New Jersey : John Wiley & Sons, Inc., 2020)
"The idea for this book is to share real world use cases that leverage people, process, and technology. The authors reveal successes using the right skillsets from people, well-defined process for data and analytics, and innovative technology for managing analyzing all healthcare touchpoints. They emphasize how unifying people, process and technology deliver results and executive sponsorship to drive continued investment for the future. This book discusses: Unifying people, process and technology for insight-driven decisions, modernizing data and analytics platforms to accommodate healthcare complexity, innovative technologies to conquer data complexity in healthcare, distributed capabilities and analytics to key stakeholders in healthcare, intelligence sharing from patient to doctor to healthcare provider, how analytics help with healthcare market analysis to gain competitive advantage, building a strong foundation for augmented intelligence (AI + human intelligence), equipping healthcare organization to prepare for the future with deep learning, machine learning and cloud computing capabilities, managing data and analytics from end-to-end from diagnosis, to treatment to provider payment"--
The demand and state of healthcare -- People -- Process -- Technology -- Unifying PPT (people, process and technology) -- The future in healthcare -- Final thoughts.
Includes index.
Description based on online resource; title from digital title page (viewed on May 22, 2020).
John Wiley and Sons
Keywords: Medical informatics -- Technological innovation; Medicine -- Data processing; x; BUSINESS & ECONOMICS / Information Management; Medicine -- Data processing